2008
DOI: 10.1088/0004-6256/136/6/2391
|View full text |Cite
|
Sign up to set email alerts
|

A Catalog of Extended Green Objects in the Glimpse Survey: A New Sample of Massive Young Stellar Object Outflow Candidates

Abstract: Using images from the Spitzer Galactic Legacy Infrared Mid-Plane Survey Extraordinaire (GLIMPSE), we have identified more than 300 extended 4.5 μm sources (Extended Green Objects (EGOs), for the common coding of the [4.5] band as green in three-color composite InfraRed Array Camera images). We present a catalog of these EGOs, including integrated flux density measurements at 3.6, 4.5, 5.8, 8.0, and 24 μm from GLIMPSE and the Multiband Imaging Photometer for Spitzer Galactic Plane Survey. The average angular se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
751
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(786 citation statements)
references
References 38 publications
34
751
1
Order By: Relevance
“…The UCHII complex is remarked with a circle. Also, the EGO discovered by Cyganowski et al (2008) is indicated. The angular resolutions are ∼1.…”
Section: Resultsmentioning
confidence: 99%
“…The UCHII complex is remarked with a circle. Also, the EGO discovered by Cyganowski et al (2008) is indicated. The angular resolutions are ∼1.…”
Section: Resultsmentioning
confidence: 99%
“…The most luminous of this group is CXO J181854.64-164749.1, discussed in Section 5.5. This source is associated with protostellar outflow activity, traced by a MIR "EGO" source (Cyganowski et al 2008) and a water maser (Sato et al 2010) in a foreground cluster on the corner of our ACIS FOV. We will present a detailed study of the X-ray spectra of these and other remarkable sources associated with high-mass stars, protostars, or IMPS in a subsequent paper.…”
Section: Science Discoveriesmentioning
confidence: 94%
“…The presence of an IRDC is an important signpost that the selected objects are indeed sites of massive star formation. The star formation activity in VVVv374 is further evident through the presence of an extremely green object (EGO; Cyganowski et al 2008). The right panel in Figure 1 shows this feature for VVVv374, highlighting the bipolar outflow traced by the EGO.…”
Section: High-amplitude Variable Stars Within Atlasgal Clumpsmentioning
confidence: 99%